Mind Skills Training Model through Experiential Learning as Guide Teacher and Islamic Counselors - Supa'at Supa'at; Khilman Rofi Azmi (FITK UIN Walisongo, 2019)
This article is aimed to create mind skills training manual books for guidance teachers and counselors to increase counseling skills theoretically and practically. Mind skill used by counselors and guides teachers in MTs 1 Kudus, MTs TBS, and Muhammadiyah Kudus, Central Java to manage and think about what they think and do. It will implicate how they react and act, communicate, and respond to their counselee or client. This article used a development approach that modified from Borg and Gall model through three phases included (1) preparation, (2) implementation, and (3) trial. The mind skills training book was developed by referring to the needs of research subjects based on the results of interviews and literature studies. The result shows that the mind skills manual book for guide teacher counselor is accepted and fulfillment with an average value of 87% in the